Return to play following injuries in pro football: insights into the real-life practices of 85 elite practitioners around diagnostics, progression strategies and reintegration processes - Buchheit, M.; King, R.; Stokes, A.; Lemaire, B.; Grainger, A.; Brennan, D.; Norman, D.; Mükinen, A.; Ruggiero, H.; Shelton, A.; Sammons, G.; Bridges, M.; et al. (Sport Performance & Science Reports, 2023)
This survey has been designed to gain insight into how practitioners approach, manage, and deliver the "return to play" process (RTP, as the overall rehabilitation process that leads to the generic idea of returning to `play`), and how MDT approach the process and decision-making in the real-life conditions of elite football (soccer). More precisely, our aim was to answer key practical questions around clinical diagnosis, the use of progression criteria, players` reintegration with the group/competition, and finally, the overall organisation of the RTP process within the MDT.